The effect of science technology engineering mathematics (STEM) learning on respiratory system topic on students’ numerical ability - Ane Laksana Lintang Rahmawati; Eni Nuraeni; Ana Ratna Wulan (Department of Biology Education, Universitas Pendidikan Indonesia, 2022)
The purpose of this study was to analyze the effect of STEM learning on students' numeracy skills. STEM learning was carried out through the activity of making a UV sterilizer prototype in one class with six groups in it. Data collection was carried out before, during, and after learning. The instruments used were written tests of numeracy skills, observation sheets, and students’ questionnaires response. The effect of learning was tested through paired sample t-test and N-gain. Data collection was carried out in one class of XI IPA at Senior High School in Bandung with 21 participating students. The results showed that STEM learning had an effect on numeracy skills, with significant results (t (21) = -5.87, p = 0.00), and moderate increase (N-gain = 0.46).